A comprehensive review of the treatment and management of Charcot spine. (December 2020) - Urits, Ivan; Amgalan, Ariunzaya; Israel, Jacob; Dugay, Chase; Zhao, Alex; Berger, Amnon A.; Kassem, Hisham; Paladini, Antonella; Varrassi, Giustino; Kaye, Alan D.; Miriyala, Sumitra; Viswanath, Omar
Charcot spine arthropathy (CSA), a result of reduced afferent innervation, is an occurrence of Charcot joint, a progressive, degenerative disorder in vertebral joints, related mostly to spinal cord injury. The repeated microtrauma is a result of a lack of muscle protection and destroys cartilage, ligaments, and disc spaces, leading to vertebrae destruction, joint instability, subluxation, and dislocation. Joint destruction compresses nerve roots, resulting in pain, paresthesia, sensory loss, dysautonomia, and spasticity. CSA presents with back pain, spinal deformity and instability, and audible spine noises during movement. Autonomic dysfunction includes bowel and bladder dysfunction. It is slowly progressive and usually diagnosed at a late stage, usually, on average, 20 years after the first initial insult. Diagnosis is rarely clinical related to the nature of nonspecific symptoms and requires imaging with computed tomography (CT) and magnetic resonance imaging (MRI). Conservative management focuses on the prevention of fractures and the progression of deformities. This includes bed rest, orthoses, and braces. These could be useful in elderly or frail patients who are not candidates for surgical treatment, or in minimally symptomatic patients, such as patients with spontaneous fusion leading to a stable spine. Symptomatic treatment is offered for autonomic dysfunction, such as anticholinergics for bladder control. Most patients require surgical treatment. Spinal fusion is achieved with open, minimally-open (MOA) or minimally-invasive (MIS) approaches. The gold standard is open circumferential fusion; data is lacking to determine the superiority of open or MIS approaches. Patients usually improve after surgery; however, the rarity of the condition makes it difficult to estimate outcomes. This is a review of the latest and seminal literature about the treatment and chronic management of Charcot spine. The review includes the background of the syndrome, clinical presentation, and diagnosis, and compares the different treatment options that are currently available.